DRY MATTER CONTENT IN POTATO TUBERS AT BACKCROSSING AND CROSSING POTATO VARIETIES - Podhaietskyi, A. A.; Kovalenko, V.M.; Hnitetskiy, M.O. (Scientific Progress & Innovations, 2019)
The importance of high dry matter content in potato varieties, especially for processing and obtaining in-dustrial products, as well as animal feed, is undeniable. To produce varieties with such characteristics, a high quality selection material is required. Interspecific potato hybrids are particularly significant in this respect, and therefore evaluating their characteristics for practical breeding purposes is relevant. The pur-pose of the study was to compare the presence of dry matter in tubers of parental forms: interspecific hybrids and their backcrosses, varieties, progeny from their crossing. The research methodology was used as gener-ally accepted for this crop. Among the parental forms, especially for high dry matter content per plant, a double back cross of a six-species hybrid 08.195/73−121.7 g/plant and a six-species hybrid 81.459s18−83.3 g/plant were distinguished. Among the varieties, the best in this respect was Verdi variety− 71.2 g/plant. The progeny of combinations was characterized by significant difference in the trait manifestations. The mini-mum value of the limits was 7.1 times, the maximum value of the limits – 2.3 times, and population hybrids – 4.2 times. The specific mutual influence of the inheritance of one male parent on the expression of dry matter content in the progeny tubers was revealed. The smallest difference in index manifestation occurred among the three combinations involving the female parent of the Podolia variety − 25.4 g/plant. The Letana variety turned out to be the best pollinator in the block of five populations with back cross 08.195/73. The opposite was true of the Meliavitsa variety. Hybrids were found in each population with a higher index manifestation than in the best male parents, and in case of female parents of Podoliia x Basis and Podoliia x Strumok, it was found in all hybrids. The same concerns the proportion of progeny with dry matter content of 100 g/plant and more. However, the proportion of material with this characteristic was smaller with the maximum value in the population of Bagriana x 89,202s79 − 75 %. A direct and high dependence (r = + 0.89) was observed only between the trait manifestation in the female parents and the middle parents. It was high and inverse between the trait manifestation in female parents and the proportion of progeny with a higher index expression than that of the best parent.